Effective Zakat Distribution: Highlighting Few Issues and Gaps in Kedah, Malaysia - Al Haq, M Ashraf; Abd. Wahab, Norazlina Binti (UNIVERSITAS ISLAM NEGERI SYARIF HIDAYATULLAH JAKARTA, 2017)
The aim of this paper is to identify what are the impediments in implementing an effective Zakah distribution in Kedah, Malaysia. Auspiciously, post-colonial Malaysia is experiencing robustness in terms of Zakah collections, as the statistics are currently signifying, but at the same breath the degree of effectiveness in Zakah distribution has not been providentially catching that optimistic evolution. And even if, the Zakah is duly distributed, the point to note is that the effectivity of that distribution has indubitably remained in question. So this gap is an issue that has been observed by the givers, and if the collection is to increase further, the issue of effectivity in Zakah distribution needs to show a healthier trend to convince these worried payers. The implications of resolving the issues discussed below may assist to enhance this sector, if timely addressed and taken applicable measures for remediation. DOI: 10.15408/aiq.v9i2.4002